New species of Atropacarus (Hoplophorella), (Acari, Oribatida, Phthiracaridae) from the Afrotropical Region - Niedbała, Wojciech; Starý, Josef (Zootaxa, 2014)
Four new species of the subgenus Hoplophorella are desccribed and identified from the Afrotropical region: Atropacarus (Hoplophorella) curtisetosus sp. nov. from Uluguru Mountains of Tanzania, Atropacarus (Hoplophorella) distinctus sp. nov. from Ambohitantely Special Reserve of Madagascar, Atropacarus (Hoplophorella) othneios sp. nov. from Ranomafana National Park of Masagascar, and Atropacarus (Hoplophorella) stenos sp. nov. from Nguru and Uluguru Mountains of Tanzania. A comparison with the most closely related species of the subgenus Hoplophorella is also presented.